Minna VIHLA. Medical Writing. Modality in Focus, Language and Computers: Studies in Practical Linguistics, Amsterdão / Atlanta, GA: Editions Rodopi B. V. 1999. vii + 170 pp. ISBN: 90-420-0708-7 - Pinto, Maria da Graça L. Castro (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
.